2007
DOI: 10.1038/sj.jid.5700733
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Metallic Nanoparticles in Human Full-Thickness Skin

Abstract: The potential and benefits of nanoparticles in nanobiotechnology have been enthusiastically discussed in recent literature; however, little is known about the potential risks of contamination by accidental contact during production or use. Although theories of transdermal drug delivery suggest that skin structure and composition do not allow the penetration of materials larger than 600 Da, some articles on particle penetration into the skin have been recently published. Consequently, we wanted to evaluate whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
233
2
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(251 citation statements)
references
References 49 publications
(60 reference statements)
12
233
2
4
Order By: Relevance
“…Fluorescence microscope images indicate that QDs were localized in the uppermost layers of the SC and the hair follicles. This is similar to other reports that found that QD621 were localized in the outer root sheath of porcine hair follicles [9], TiO 2 microparticles and polystyrene nanoparticles distributed near orifices in human hair follicles [1,17], and metallic nanoparticles less than 10 nm were capable of penetrating the SC and hair follicles [18]. QDs can work their way between the corneocytes of the stratum corneum and penetrate deep in the epidermis and dermis of an in vivo model with UVR penetration exacerbation [10].…”
Section: Discussionsupporting
confidence: 80%
“…Fluorescence microscope images indicate that QDs were localized in the uppermost layers of the SC and the hair follicles. This is similar to other reports that found that QD621 were localized in the outer root sheath of porcine hair follicles [9], TiO 2 microparticles and polystyrene nanoparticles distributed near orifices in human hair follicles [1,17], and metallic nanoparticles less than 10 nm were capable of penetrating the SC and hair follicles [18]. QDs can work their way between the corneocytes of the stratum corneum and penetrate deep in the epidermis and dermis of an in vivo model with UVR penetration exacerbation [10].…”
Section: Discussionsupporting
confidence: 80%
“…Wide-range applications stimulated intensive study of interaction of nanoparticles with a living tissue and in particular the penetration and migration of the nanoparticles inside the tissue. Some authors suggested that the processes governing the penetration of reactive radicals (see extensive discussion of these effects in Section 4) [29] and those governing nanoparticles are not the same [30], making a good case for penetration selectivity argument. In addition, penetration efficacy of nanoparticles inside various tissues is distinctly different.…”
Section: Interaction Of Nanoparticles With Cellsmentioning
confidence: 99%
“…The above synergy takes advantage of the superior capability of nanoparticles to penetrate through the skin barrier [30], thus liberating plasma from its limitation as an intrinsically topical technique. The potential specificity of nanoparticles to attach to diseased cells as against healthy cells [136] offers selectivity, and the use of ROS or RNS carried by nanoparticles as the main agent against either cancer cells or pathogens reduces the reliance on toxic materials (e.g.…”
Section: Synergy In Reaction Chemistrmentioning
confidence: 99%
“…Small molecules are able to move freely within the intercellular spaces and diffusion rates are governed largely by their lipophilicity, but also physicochemical properties such as molecular weight or volume, solubility and hydrogen bonding ability [Potts & Guy 1995]. However, the free movement of macromolecules or www.intechopen.com [Baroli et al 2007]. This suggests that for such materials, the SC could present an additional barrier that is not present for small molecules.…”
Section: Skin As a Site For Particle Deliverymentioning
confidence: 98%